Principles of reforming an agile-compliant performance appraisal - Mawarny Md. Rejab; Mazni Omar; Mazida Ahmad; Syahida Hassan (Institute of Advanced Engineering and Science, 2019)
This paper presents principles of reforming an Agile-compliant performance appraisal. In this study, several semi-structured interviews have been carried out and discovered eight principles for reforming an Agile-compliant performance appraisal for Agile teams. Performance appraisal for software engineers in an Agile software development environment is complex and different from the traditional software development. Performance appraisal should be aligned to Agile values, principles, and practices, which advocate interactions, collaborations, teamwork, and knowledge transfer among Agile team members. Therefore, a transition to Agile Software Development requires the implementation of Agile-compliant performance appraisal. These principles embark the proper practices and guidance to support management and Agile teams in deriving and implementing an Agile-compliant performance appraisal. Therefore, the emerged principles can be a baseline in generating an Agile-compliant performance appraisal to assess Agile team members in a fair and consistent manner. This indirectly increases motivation amongst team members and tends to produce capable workforce to perform at a higher level.